Integrating Oral PrEP Into Family Planning Services for Women in Sub-saharan Africa: Findings From a Multi-Country Landscape Analysis - Bhavaraju, Neeraja; Wilcher, Rose; Regeru, Regeru Njoroge; Mullick, Saiqa; Mahaka, Imelda; Rodrigues, Jessica; Mason, Jennifer; Schueller, Jane; Torjesen, Kristine (Frontiers in Reproductive Health, 2021)
Integration of HIV and family planning (FP) services is a renewed focus area for national policymakers, donors, and implementers in sub-Saharan Africa as a result of high HIV incidence among general-population women, especially adolescent girls and young women (AGYW), and the perception that integrating HIV pre-exposure prophylaxis (PrEP) into FP services may be an effective way to provide comprehensive HIV and FP services to this population. We conducted a focused desk review to develop a PrEP-FP integration framework across five key categories: plans and policies, resource management, service delivery, PrEP use, and monitoring and reporting. The framework was refined via interviews with 30 stakeholders across seven countries at varying stages of oral PrEP rollout: Kenya, Lesotho, Malawi, South Africa, Uganda, Zambia, and Zimbabwe. After refining the framework, we developed a PrEP-FP integration matrix and assessed country-specific progress to identify common enablers of and barriers to PrEP-FP integration. None of the countries included in our analysis had made substantial progress toward integrated PrEP-FP service delivery. Although the countries made progress in one or two categories, integration was often impeded by lack of advancement in other areas. Our framework offers policymakers, program implementers, and health care providers a road map for strategically assessing and monitoring progress toward PrEP-FP integration in their contexts.